Пашкевич Г.О., Відейко М.Ю. Рільництво племен трипільської культури - Отрощенко, В.В.; Горбаненко, С.А. (Археологія, 2008)
Рецензія на: Пашкевич Г.О., Відейко М.Ю. Рільництво племен трипільської культури. - К., 2006. — 147 с.